Determination of the electrophoretic mobilities and zeta potentials of gas bubbles in aqueous solutions in the presence of frothers - Sayo, Rachelle Anne V. (2012)
This study aims to measure the electrophoretic mobilities and zeta-potentials of gas bubbles in aqueous environment as a function of electrolyte (KNO3) concentration in the presence and absence of frothers as surfactants. The frothers used are pine oil and ethylene glycol. A modified electrophoretic apparatus was designed to generate microbubbles by hydrolysis upon the application of voltage across two (2) platinum wires inserted in an electrophoretic cell. The bubbles move in a projectile motion due to buoyancy and electrophoresis. Only the horizontal component of the velocity was considered for the electrophoretic mobility calculation and was related to the zeta potential using Smoluchowski's equation. In the absence of frothers, the iso-electric point (i.e.p.) of gas bubbles is at the vicinity of pH 4 and the occurrence of charges at the surface of bubbles is due to the increased amounts of hydroxyl (OH-) ions. The magnitude of the zeta potentials of gas bubbles decreased as the concentration of the electrolyte is increased due to the compression of electrical double layer (EDL) and neutralization of the surface charges. The increased addition of frothers resulted in the following: 1) decrease in the bubbles' size and also caused significant changes in the size distribution of bubbles; 2) decrease in the surface tension of the bubbles produced; and 3) increase in the mobility of the bubbles as reflected in the corresponding increase in the magnitude of the zeta potential of bubbles regardless of the type of frother used.